Clinical Germline Testing Results of Men With Prostate Cancer: Patient-Level Factors and Implications of NCCN Guideline Expansion. (23rd March 2021) - Greenberg, Samantha E.; Hunt, Trevor C.; Ambrose, Jacob P.; Lowrance, William T.; Dechet, Christopher B.; O'Neil, Brock B.; Tward, Jonathan D.
Abstract : PURPOSE: Germline likely pathogenic or pathogenic variants (PVs) have been identified in up to 17% of men with prostate cancer (PC) and may drive disease severity or be targetable by novel therapies. National Comprehensive Cancer Network (NCCN) guidelines encouraging germline testing in metastatic PC were recently expanded to include all men with high-risk, very high-risk, or regional PC. Our aim was to assess the impact of expanded NCCN guidelines on the detection rate of germline PVs and to determine patient-level factors associated with a PV germline testing result. PATIENTS AND METHODS: Men with PC underwent multigene germline genetic testing for PVs from June 2016 to December 2018, and trends were compared. The association of patient-level factors with a PV germline testing result, where ≥ 1 PV was identified, was assessed using analysis of variance and univariate logistic regression. Sensitivity analyses were limited to clinically actionable variants and those associated with disease severity or progression ( BRCA1/2 and ATM ). RESULTS: Of 408 men undergoing germline testing, 42 (10.3%) men had PVs and 366 (89.7%) men did not have PVs identified. The proportion of men identified with a germline PV remained stable following testing criteria expansion (9.4% v 10.6%, P = .73). No patient-level factors were significantly associated with increased odds of a PV germline testing result, including age at diagnosis, race, pretreatment prostate-specific antigen, Gleason grade group, NCCN risk group, and family history of cancer (breast and/or ovarian, prostate, or any cancer). CONCLUSION: This study demonstrated a stable PV detection rate in men with PC using expanded criteria aligned to the updated NCCN testing guidelines. However, we did not find strong evidence to suggest that patient-level factors are associated with PV germline testing results. These findings support the recent expansion of NCCN germline testing guidelines in PC.